Effects of Immediate or Delayed Estradiol on Behavior in Old Menopausal Macaques on Obesogenic Diet - Kristine Coleman; Nicola D. Robertson; Adriane Maier; Cynthia L. Bethea (Journal of Obesity)
Macaques have served as effective models of human disease, including pathological processes associated with obesity and the metabolic syndrome. This study approached several questions: (1) does a western-style diet (WSD) contribute to sedentary behavior or is sedentary behavior a consequence of obesity and (2) does estradiol (E) hormone therapy offset WSD or ameliorate sedentary behavior? We further questioned whether the timing of E administration (immediately following hysterectomy, ImE; or after a 2-year delay, DE) would impact behavior. Focal observations were taken on the animals in social housing over a period of 2.5 years before and after initiation of the WSD and hysterectomy. In addition, anxiety was assessed through the Human Intruder and Novel Object Tests. All animals gained weight, but ImE delayed the time to maximum weight achieved at 18 months. Over the course of the study, ImE-treated monkeys spent more time “alone” and less time in “close social” contact than placebo-controls. The DE-treated monkeys were not different from placebo-controls in these 2 outcomes. The placebo-control group exhibited more “self-groom” behavior, an indicator of anxiety, than did the ImE-treated group, and DE-treated animals approached levels observed in the ImE-treated animals. All animals exhibited an increase in “consume” behavior over time with no statistical difference between the groups. By the end of the protocol, the placebo-control group exhibited less activity compared to ImE + DE-treated animals combined. Animals also showed increased anxiety after starting on the WSD in the Human Intruder Test and the Novel Object Test. In summary, the data indicated that WSD per se promoted increased consummatory behavior, sedentary behavior, and anxiety-type behaviors, whereas ImE promoted activity. Thus, WSD may precipitate the behaviors observed in humans who then become obese, sedentary, anxious, and socially isolated. ImE replacement ameliorates some of these behaviors, but not all.